Yurisprudensi Ulama Klasik Dalam Putusan Akad Murabahah di Pengadilan Agama Dari Tahun 2014-2024 - Septiarti, Mela; Mursal, Mursal; Fauzi, Muhammad; Moosa, Riyad (ASAS, 2025)
The rapid development of Islamic banking in Indonesia has rendered murabahah contracts the most dominant financing scheme; however, their implementation has frequently generated legal disputes adjudicated by the Religious Courts, particularly those concerning default, the determination of profit margins, the application of penalty clauses, and the execution of collateral auctions. This study aims to examine the patterns of murabahah dispute resolution by the Religious Courts in Indonesia during the 2014–2024 period by analyzing the application of classical Islamic jurisprudence (fiqh) and ushul fiqh principles in judicial reasoning. Employing a normative–empirical approach, this research applies content analysis to 62 court decisions obtained from official sources using the keyword “murabahah.” The findings indicate that default-related disputes constitute the most dominant category, accounting for 41 decisions. In their legal reasoning, judges refer to the Compilation of Sharia Economic Law (KHES) and classical fiqh principles, particularly the prohibition of riba in assessing the legitimacy of profit margins and penalties, the principle of justice (al-‘adl) in balancing the rights and obligations of the parties, and the concept of maslahah in evaluating the implications of judicial decisions for the interests of the parties and the stability of Islamic banking. Nevertheless, the study identifies inconsistencies in judicial decisions arising from divergent judicial interpretations. Therefore, this study recommends strengthening judges’ understanding of fiqh mu‘amalah, harmonizing legal interpretations, and enhancing contractual transparency to reinforce legal certainty in Islamic banking practices in Indonesia.